HAK DAN PERLINDUNGAN ANAK PERSPEKTIF (STUDI LIVING HADIS DI DESA HUTA BAHTOBU KOTA PEMATANG SIANTAR) - Noval Al-Naviz Siregar; Nur Aisah Simamora (SHAHIH (Jurnal Ilmu Kewahyuan), 2025)
Child protection is a universal issue that demands serious attention, particularly in the socio-religious context of Muslims, which is based on the values of the hadith. The increasing number of cases of violence, neglect, and exploitation of children in various regions of Indonesia, including in Huta Bahtobu Village, Pematang Siantar City, indicates a gap between normative Islamic teachings on children’s rights and the prevailing social reality. This study aims to analyze children’s rights and protection from the perspective of the hadith and to explore how the community’s understanding and practice of these hadith values are manifested in daily life through a living hadith approach. The method used is descriptive qualitative with a phenomenological approach. Data were obtained through observation, in-depth interviews with religious leaders, parents, and the community, and documentation of religious practices that reflect child protection. Data analysis was carried out through stages of reduction, thematic categorization, and interpretation of the meaning of the hadith in the local social context. The results show that the Huta Bahtobu community understands the hadith on children's rights, especially in the dimensions of affection, education, and parental moral responsibility. However, its implementation is often symbolic and has not been fully internalized in the local social and cultural system. The values of the hadith concerning respect for children’s natural instincts, meeting their physical and spiritual needs, and prohibiting violence are practiced through religious activities such as family religious studies, religious study groups, and local traditions that emphasize the role of parents as moral protectors of children. The implications of this research emphasize that strengthening the understanding of the hadith in terms of children’s rights and protection can form the basis for the formation of a more humane and just society in modern society.